The Chankas and the priest : a tale of murder and exile in highland Peru - Hyland, Sabine, 1964- (The Pennsylvania State University Press, 2016)
"Presents the story of the Chanka people of Peru, from the fifteenth to the eighteenth centuries, told through a narrative of the crimes committed by a priest, Juan Bautista de Albadán, in the early 1600s"--Provided by publisher